2006
DOI: 10.1177/00238309060490040201
|View full text |Cite
|
Sign up to set email alerts
|

Phonetics and Phonology of Thematic Contrast in German

Abstract: It is acknowledged that contrast plays an important role in understanding discourse and information structure. While it is commonly assumed that contrast can be marked by intonation only, our understanding of the intonational realization of contrast is limited. For German there is mainly introspective evidence that the rising theme accent (or topic accent) is realized differently when signaling contrast than when not. In this article, the acoustic basis for the reported impressionistic differences is investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
104
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(125 citation statements)
references
References 54 publications
(84 reference statements)
13
104
1
Order By: Relevance
“…In this context it is also interesting to note that previous studies on German have found similar patterns: Braun (2006) reports that speakers produced mainly (! )H +L* nuclear accents in her reading experiment.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…In this context it is also interesting to note that previous studies on German have found similar patterns: Braun (2006) reports that speakers produced mainly (! )H +L* nuclear accents in her reading experiment.…”
supporting
confidence: 69%
“…While the agreement on the presence or absence of a pitch accent was reasonable (81% in the English study, 87% in the German study), agreement on the type of pitch accent was much lower (64% in the ToBI experiment and only 51% in the GToBI experiment). Considerable inconsistency is also reported by Braun (2006), who asked trained labellers to annotate topical referents in German sentences choosing only among the three accents H*, L+H*, and L*+H.…”
Section: Prosodic Annotationmentioning
confidence: 99%
“…It consists of two accents, the first one rising, the second one falling, and a high pitch between the two ( Figure 1a). This contour is an instance of an intonational ''false friend'' (same form but different function across languages): it has been described as a neutral intonation contour for Dutch (Cohen & 't Hart, 1967;'t Hart, Collier, & Cohen, 1990), but is associated with contrast in German (e.g., Braun, 2005Braun, , 2006Büring, 1997;Krifka, 1998;Mehlhorn, 2001;Steube, 2001;Wunderlich, 1991). This difference in the marking of intonational meaning is especially striking, since Dutch and German are two closely related Western Germanic languages.…”
Section: Introductionmentioning
confidence: 99%
“…If the same F 0 maximum value occurred two or more times within a high F 0 section, which happened in only 9 (i.e., 4.8%) of our 186 tokens, then we applied a common method and defined the first value as the peak maximum (e.g., Braun 2005). Note that the rising and falling F 0 ranges were not calculated with reference to the F 0 -peak maximum.…”
Section: Acoustic Analysismentioning
confidence: 99%